Interface properties of Ti3SiC2/Al2O3 ceramics: Combined experiments and first-principles calculations. Issue 5 (1st March 2021) - Ji, Jun; Zhang, Liu; Yu, Jinman; Lee, William E.; Middleburgh, Simon C.; Li, Dechun; Wang, Xuye; Li, Qinggang; Wang, Zhi; Shi, Guopu; Chen, Fei
Abstract: The synthesis, characterization, and first-principles calculations of Ti3 SiC2 /Al2 O3 ceramics were reported. X-ray diffraction measurements showed that the composite ceramics were highly pure. Scanning electron microscopy and transmission electron microscopy were used to characterize the interface information for Ti3 SiC2 and Al2 O3 crystals. Surface energies and interface properties were calculated using the first-principles method. The results suggested that Ti3 SiC2 with Ti terminations and Al2 O3 with O terminations are more stable than other terminations crystals. Thus powerful attraction between the coordinatively unsaturated Ti and O atoms on the Ti3 SiC2 ∥Al2 O3 interface would result in higher work of adhesion (Wad) and shorter boundary distance, demonstrating the intercrystalline strengthening of Ti3 SiC2 /Al2 O3 composite ceramics.